2015
DOI: 10.1097/sa.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Requirements in Surgical Oncology Patients

Abstract: F or patients with solid tumors, surgery is often the main treatment, but the issue of the potential benefits and risks of red blood cell (RBC) transfusions during surgery remains. Although previous studies have indicated that a restrictive RBC transfusion strategy is as safe and effective as a liberal one, patients with cancer are not included in most such trials. This parallel-group, doubleblind, superiority, randomized controlled trial was undertaken to determine whether a restrictive strategy of RBC transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 2 publications
3
39
0
3
Order By: Relevance
“…Similar findings were also reported in a large Korean study on septic patients by Park et al (13) who showed better outcome in septic patients who had received blood transfusions. In parallel similar results have been found in other groups of surgical patients including cardiac surgery and cancer patients showing the benefit of transfusing blood (14,15). All these findings underscore the general conclusion that avoiding anemia by targeting a conservative (eg 9 g/dL) transfusion trigger is with the current blood received from modern blood banks, a safe procedure of benefit especially for the elderly patient at risk.…”
Section: Nüzhet Mert şEntürk Editorsupporting
confidence: 73%
“…Similar findings were also reported in a large Korean study on septic patients by Park et al (13) who showed better outcome in septic patients who had received blood transfusions. In parallel similar results have been found in other groups of surgical patients including cardiac surgery and cancer patients showing the benefit of transfusing blood (14,15). All these findings underscore the general conclusion that avoiding anemia by targeting a conservative (eg 9 g/dL) transfusion trigger is with the current blood received from modern blood banks, a safe procedure of benefit especially for the elderly patient at risk.…”
Section: Nüzhet Mert şEntürk Editorsupporting
confidence: 73%
“…Two recent systematic reviews in cardiac surgery [19] and in perioperative transfusion practice (including cardiac surgery) [20] reported higher mortality with a restrictive transfusion threshold. Our systematic review [21] found only 11 blood transfusion threshold randomized controlled trials (RCTs) that included patients with co-existing CVD, either as the whole population [10,[22][23][24], as a pre-defined subgroup [9,11,25] or as a high proportion of patients [14,[26][27][28]. We found no evidence of a difference in 30-day mortality between restrictive and liberal transfusion thresholds.…”
Section: Evidence In Patients With Co-existing Cardiovascular Diseasementioning
confidence: 71%
“…One possible reason was the low sensitivity of routine laboratory parameters to indicate a coagulation disorder and the waiting period for the result. Harmful or ineffective plasma overuse [13][14][15] and prophylactic use [16][17][18] in critical ill patients could be overcome by coagulation concentrates [19].…”
Section: Discussionmentioning
confidence: 99%